MONO COMPONENT ADDITIONAL FOOD IN CHILDREN WITH CYSTIC FIBROSIS - E.M. Shadrina; S.A. Boykov; N.S. Shatokhina ("Paediatrician" Publishers LLC, 2010)
Authors analyze an experience of nutrition with mono component additional food «Gerber» in 15 infants with cystic fibrosis. They estimated a safety of additional food and its effectiveness via proper individual nutrition list and laboratory data (changes in faeces analysis and state of intestinal biocoenosis). Key words: children, cystic fibrosis, additional food. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(2):99-102)